2015
DOI: 10.1063/1.4926829
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of solvation and desolvation of rubidium attached to He nanodroplets

Abstract: The real-time dynamics of photoexcited and photoionized rubidium (Rb) atoms attached to helium (He) nanodroplets is studied by femtosecond pump-probe mass spectrometry. While excited Rb atoms in the perturbed 6p-state (Rb * ) desorb off the He droplets, Rb + photoions tend to sink into the droplet interior when created near the droplet surface. The transition from Rb + solvation to full Rb * desorption is found to occur at a delay time τ ∼ 600 fs for Rb * in the 6pΣ-state and τ ∼ 1200 fs for the 6pΠ-state. Rb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 42 publications
8
50
1
Order By: Relevance
“…In particular, for λ = 415 nm, which corresponds to excitation of mainly the 6pΠ 3/2 -state, the simulated rising edges of both the mean speed and the [RbHe] + ion yield match the experimental results very well [panels e) and h)]. The better agreement of experiment and simulation as compared to our previous model calculations [28] is mainly due to the different initialization procedure of the excited wave packet, which supports the model assumptions made in the present approach. Furthermore, the simulated widths σ and skewnesses γ match the experimental values quite well for long delays ∆t.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In particular, for λ = 415 nm, which corresponds to excitation of mainly the 6pΠ 3/2 -state, the simulated rising edges of both the mean speed and the [RbHe] + ion yield match the experimental results very well [panels e) and h)]. The better agreement of experiment and simulation as compared to our previous model calculations [28] is mainly due to the different initialization procedure of the excited wave packet, which supports the model assumptions made in the present approach. Furthermore, the simulated widths σ and skewnesses γ match the experimental values quite well for long delays ∆t.…”
Section: Resultssupporting
confidence: 73%
“…Due to the conservation of energy in the wave packet propagation, this final speed distribution relates to an initial spatial distribution |ψ * (R)| 2 of the wave packet on the repulsive PEC at short distances. This approach differs from the one we used previously for a mixed quantum-classical simulation [28]. There, the wave packet propagation was initialized based on the spectral profile of the pump laser pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(77) yields the results summarised in Photoexcitation and photoionisation of Rb atoms attached to helium droplets has been studied in real-time dynamics experiments. 267 It was shown that excitation of Rb atoms from the 5s to the 6p states leads to their detachment. Upon subsequent ionisation of the excited Rb atom (Rb * ), the interaction with helium becomes attractive.…”
Section: Interaction Of Impurities With Vortex Linesmentioning
confidence: 99%
“…The critical time τ c separating these processes is called the fall-back time. 267 Recently, this study has been extended to the Rb 5p ← 5s transition. 31 Both transitions have been simulated with TDDFT as described in Sec.…”
Section: Interaction Of Impurities With Vortex Linesmentioning
confidence: 99%